(untitled) (Research, Society and Development, 2022)
This research aimed to analyze the opinion, academic experiences, and professional perspectives of undergraduate students of the Dentistry course at a Higher Education Institution on the importance of inserting the dental surgeon in the hospital environment. This is a field study with a descriptive character, a quantitative approach and a cross-sectional method carried out with students from the 9th and 10th period of the dentistry course, using a specific and structured questionnaire as a data collection instrument, available online on Google Forms platform, containing 10 questions related to the experiences lived by the students. 30 students participated in the research, 18 regularly enrolled in the 10th period and 11 enrolled in the 9th period, 96.7% declared that they knew how to clearly define the role of the Dental Surgeon in the hospital environment, nevertheless, 60% stated that the content taught in a theory is not enough to know what Hospital Dentistry is all about; 87.6% had some practical experience in this context, although, 90% stated that the workload of the internship is not sufficient to become aware of the role of the dentist in a hospital context, however, 86.7% felt were encouraged to look for other sources of knowledge on the subject and 53.3% said they were interested in joining this area of ​​Dentistry professionally. It was concluded that the students showed interest in Hospital Dentistry and felt motivated to enter this area professionally. Meantime, they consider this curricular unit’s practical and theoretical workload insufficient to nurture comprehensive knowledge on the subject.